Epoxy emulsions stabilized with reactive bio-benzoxazine surfactant from epoxidized cardanol for coatings. (August 2016) - Ambrožič, Rok; Šebenik, Urška; Krajnc, Matjaž
Graphical abstract: Highlights: Novel bio-based surfactant, with benzoxazine structure, was designed and developed. Synthesized benzoxazine surfactant stabilizes epoxy aqueous emulsions efficiently. Bio-based ESO was used to obtain waterborne epoxy formulations. The addition of the surfactant improved thermomechanical properties of coatings. Amine cured epoxy coatings containing high amount of ESO had high Tg values. Abstract: Epoxidized cardanol was used as a starting material for the development of a novel bio-based benzoxazine surfactant (BOX). The designed surfactant was used as a stabilizer for epoxy aqueous emulsions. As dispersed phase two epoxy resins were used; synthetic bisphenol A diglycidy ether type epoxy resin (EP) and bio-renewable epoxidized soybean oil (ESO). Formation and stability of aqueous emulsions were studied by investigating particle size and distribution and rheological behavior. Copolymer films (coatings), produced by drying the emulsions, were cured at elevated temperature. To ensure a highly crosslinked structure of thermosetting films amine curing agent (AM) was used. Benzoxazine surfactant showed excellent compatibility with both epoxy resins and effectively copolymerized with both of them. The introduction of polybenzoxazine into the epoxy network improved the thermomechanical properties (higher value of storage modulus and higher crosslink density) of neat epoxy resins. The glass transition temperature was reduced only slightly.